2012
DOI: 10.1128/cvi.00054-12
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Polioviruses among University Students in Northern Italy

Abstract: The widespread use of poliovirus vaccination schemes has led to a marked decline in the incidence of paralytic poliomyelitis worldwide, but wild poliovirus is still endemic in some developing countries, and in 2009 a total of 23 countries reported at least 1 case of poliomyelitis caused by wild-strain polio viruses. A serological survey was thus conducted on the immunological status against polioviruses of 318 young adults, classified by their country of origin. Immunity to poliomyelitis was assessed by neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…Similarly, a reduction in neutralising antibodies levels according to age was found in university students whether Italian or from outside EU. 7 Seropositivity rates very close to 100% were observed in Apulian children from zero to 15 years old, with the lowest titres in infants in the first year of life who have not concluded immunisation and a decline of GMT associated with age, particularly for PV3 again. 5 As the risk of reintroduction of the virus is strongly reduced but still not completely eliminated, the low and decreasing levels of immunity in adolescents represent a matter of concern.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, a reduction in neutralising antibodies levels according to age was found in university students whether Italian or from outside EU. 7 Seropositivity rates very close to 100% were observed in Apulian children from zero to 15 years old, with the lowest titres in infants in the first year of life who have not concluded immunisation and a decline of GMT associated with age, particularly for PV3 again. 5 As the risk of reintroduction of the virus is strongly reduced but still not completely eliminated, the low and decreasing levels of immunity in adolescents represent a matter of concern.…”
Section: Discussionmentioning
confidence: 91%
“…Two cases of imported wild viruses were detected in not vaccinated children coming from Iran (1984) and India (1988). 6,7 A sequential schedule composed of two doses of IPV (at 3 and 5 months) and two of OPV (at 11 months and 3 years of age) was employed since 1999. Since July 2002, a four doses IPV schedule was adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Une enquête sérologique menée en Italie a montré que la proportion des sujets séropositifs au PVS de type décroit avec l’âge. Une étude basée sur une évaluation sérologique du niveau d'immunité des sujets aurait été plus fiable [9, 10]. …”
Section: Discussionunclassified
“…When German medical students in Bonn were tested by microneutralization assay for antipolio antibodies types 1, 2, 3 during 2004-2006 and 2008-2010, triple-seropositivity was present in only 57 and 64%, respectively [33]. Another study found seronegativity (defined as antibody titers ≤1:8) in university students in northern Italy in significant proportions: 26.7% for poliovirus type 1, 2.8% for type 2 and 22.6% for type 3 [34]. Seropositivity declined with older age, especially in the Italian group [34].…”
Section: Routine Vaccinesmentioning
confidence: 94%
“…Another study found seronegativity (defined as antibody titers ≤1:8) in university students in northern Italy in significant proportions: 26.7% for poliovirus type 1, 2.8% for type 2 and 22.6% for type 3 [34]. Seropositivity declined with older age, especially in the Italian group [34]. Business travelers, particularly those who anticipate travel to many emerging market economies, should be assessed for their polio vaccine status.…”
Section: Routine Vaccinesmentioning
confidence: 95%